Authentic gender development in non-binary children - Salinas-Quiroz, Fernando; Sweder, Noah (Frontiers in Sociology, 2023)
At present, the conceptualization of gender as a spectrum as well as non-binary identities have become increasingly visible and embraced. We are using non-binary as an umbrella term that refers to individuals who self-identify as a gender outside the gender binary, and/or who do not identify as always and completely being just a man or a woman. Our goal is to begin to create a framework for understanding gender development in non-binary children ages 0 to 8, since previous models have operated on cissupremacist assumptions, not applicable to non-binary people. As there is virtually no empirical data on the subject, we conducted a thorough literature review of current gender development theories and used our positionality as non-binary researchers to postulate two minimum criteria for non-binary gender identification: that a child learns about the existence of non-binary identities, and that they do not identify with the definitions they have been taught of what a boy or girl is. Children can learn about non-binary identities through media and knowledgeable community members and can develop “gender traits” authentically and come to identify as non-binary through biological predispositions, parental support, modeling, and being in peer groups that are supportive of identity exploration. Yet, children are not simply a product of their nature and nurture, as evidence has shown that humans are active agents in their gender development from a young age.